(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2009)
An investigation was carried out at the Bangladesh Council of Scientific and Industrial Research (BCSIR) Laboratories. Binodpur Bazar, Rajshahi during the period November 2006 to March 2007 to evaluate the physiological and biochemical composition of five cultivars of ber (jujube). Among the fruit cultivars, Thai kul produced the largest fruits (51.85 g each) having the highest pulp (92.38%) and juice (60%) and also the lowest vitamin C content (21.13 mg/100g). The fruit weight of the other cultivars varied from 9.6 0 to 45.09g. The seed weight ranged from 6.38 to 15.00%. Sugar content varied from 6.25% to 9.72% and starch content ranged from 0.715% to 0.963%. The apple kul had the highest qualitative score through organoleptic test while Thai kul had the lowest. The highest edible portion (pulp content) was in Narikeli kul (93.61%) and that of lowest in Apple kul (85.38%) and Local kul (85.38%) respectively. Considering all, fruit characters and yield are potential. Keywords: Ber, Cultivar, Fruit characters, Quality, Yield. DOI: 10.3329/bjsir.v44i2.3678 Bangladesh J. Sci. Ind. Res. 44(2), 229-232, 2009